Up‐regulation of GhTT2‐3A in cotton fibres during secondary wall thickening results in brown fibres with improved quality. Issue 10 (2nd April 2018) - Yan, Qian; Wang, Yi; Li, Qian; Zhang, Zhengsheng; Ding, Hui; Zhang, Yue; Liu, Housheng; Luo, Ming; Liu, Dexin; Song, Wu; Liu, Haifeng; Yao, Dan; et al.
Summary: Brown cotton fibres are the most widely used naturally coloured raw materials for the eco‐friendly textile industry. Previous studies have indicated that brown fibre pigments belong to proanthocyanidins (PAs) or their derivatives, and fibre coloration is negatively associated with cotton productivity and fibre quality. To date, the molecular basis controlling the biosynthesis and accumulation of brown pigments in cotton fibres is largely unknown. In this study, based on expressional and transgenic analyses of cotton homologs of Arabidopsis PA regulator TRANSPARENT TESTA 2 (TT2) and fine‐mapping of the cotton dark‐brown fibre gene ( Lc1 ), we show that a TT2 homolog, GhTT2‐3A, controls PA biosynthesis and brown pigmentation in cotton fibres. We observed that GhTT2‐3A activated GhbHLH130D, a homolog of Arabidopsis TT8, which in turn synergistically acted with GhTT2‐3A to activate downstream PA structural genes and PA synthesis and accumulation in cotton fibres. Furthermore, the up‐regulation of GhTT2‐3A in fibres at the secondary wall‐thickening stage resulted in brown mature fibres, and fibre quality and lint percentage were comparable to that of the white‐fibre control. The findings of this study reveal the regulatory mechanism controlling brown pigmentation in cotton fibres and demonstrate a promising biotechnological strategy to break the negative linkage between coloration and fibre quality and/or productivity.